Pelatihan Pemanfaatan Sulur Keladi Menjadi Camilan yang Menyehatkan pada Calon Wirausahawan di Kota Banjarbaru - Vitria, Aida; Abdurrahim, Abdurrahim; Putera , Roja; Jumiati, Jumiati; Purboyo, Purboyo; Zainab, Siti (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing snack consumption trend in Indonesia, along with the availability of processed snacks that are high in sugar, fat, and sodium but low in fiber, poses a significant challenge to digestive health. More than 40% of the global population experiences digestive disorders, often related to unhealthy eating patterns and low fiber intake. In response to this issue, an innovative healthy snack called TaroStik, made from taro vines (Colocasia esculenta) rich in fiber and nutrients, has been developed. This product comes in two forms, sticks and chips, with three flavor variants (salty, sweet, and spicy), offering a healthy snacking experience without sacrificing taste. Training on utilizing taro vines to create TaroStik was conducted in Banjarbaru, involving prospective entrepreneurs with a combined approach of theory, hands-on practice, and group discussions. Participants were trained from material selection, processing (peeling, soaking, steaming, frying), packaging, to social media marketing simulation. As a result, most participants were able to independently produce TaroStik, with some expressing intentions to continue production at a home scale. TaroStik not only provides a digestive health solution through natural snacks free of preservatives but also brings positive impacts in three areas: economy (creating business opportunities based on local ingredients), environment (reducing agricultural waste), and nutrition (increasing healthy food consumption). This innovation embodies the principles of green economy and sustainable entrepreneurship, opening new business opportunities and improving community welfare.